Organization of working time in public authorities and influence of personal qualities of employees on organizational efficiency - Krasnykov, Yevgen (Management and Entrepreneurship: Trends of Development, 2023)
Effective management of a public service organization is characterized by an extremely high degree of complexity, dynamism and uncertainty. The ability to adapt in a timely manner to changes that cause factors of influence is the main condition for the effective operation of the organization and the high quality of their services. That is why the study of the influence of the internal environment on the effectiveness of managing a public organization is of particular relevance. To analyze the internal subjective factors affecting the efficiency of a public organization, in this work we include: the organization of the work of a public authority, the individual qualities of personnel, as well as the degrees of their professional competence.The article studies the organization of working time in public authorities. Working time in each organization is an extremely important resource, so the level and quality of its use require systematic research. Understanding the structure of working time in a public organization allows you to establish how effectively it provides services. Analysis of the results of the study shows that the main costs of working hours of civil servants are associated with secondary work, which ensures the fulfillment of the main tasks assigned to the organization.One of the indicators of the effective work of a public organization is the level of formation of the psychological climate and personal qualities of the staff. The author shows the dependence of the level of effective work of public organizations on the psychological atmosphere in the organization, as well as the influence of the personal qualities of its employees.The level of professional competence of personnel is his knowledge, skills and personal experience. Being competent means being able to mobilize in public service in a certain situation the knowledge and experience gained. The author substantiated that professional competence should be constantly developed and improved.On the basis of systematization of internal factors, current directions that affect the efficiency of the public organization are allocated.JEL Classification: H79, J20, M10